2016
DOI: 10.1007/s00384-016-2635-1
|View full text |Cite
|
Sign up to set email alerts
|

Complication and remission rates after endoscopic argon plasma coagulation in the treatment of haemorrhagic radiation proctitis

Abstract: Purpose The management of haemorrhagic radiation proctitis is challenging because of the necessity for repeated intervention. The efficacy of argon plasma coagulation has been described before but the optimum treatment strategy remains debatable. This is a review of our experience over a decade treating patients with haemorrhagic radiation proctitis and their follow-up. Methods This is a retrospective review of consecutive patients who underwent argon plasma coagulation for haemorrhagic radiation proctitis bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
1
17
1
Order By: Relevance
“…The efficacy of APC in our study seemed to be less than that observed in some prior studies[22-24]. Two main reasons may contribute to this.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The efficacy of APC in our study seemed to be less than that observed in some prior studies[22-24]. Two main reasons may contribute to this.…”
Section: Discussioncontrasting
confidence: 85%
“…In a series of 50 patients, Swan et al[26] found that the endoscopic grade did not predict the likelihood of treatment success. A study by Siow et al[22] also suggested that endoscopic grading was not a predictor of the number of APC sessions needed to achieve hemostasis. However, Zinicola et al[18] suggested that endoscopic severity could predict the success of APC.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies in this systematic review used the firstgeneration APC machine (ICC/APC 300 system; Erbe Elektromedizin, Tuebingen, Germany), which may not be available in most endoscopy units. 16,18,19,21,[24][25][26]28,29,32,33,37,39,40,44,46,48 Only 3 studies used the second-generation APC machine (VIO APC/APC 2; Erbe Elektromedizin). 17,31,46 Comparative studies.…”
Section: Argon Plasma Coagulationmentioning
confidence: 99%
“…Apart from medical therapies, hyperbaric Oxygen appears to be an effective therapy for radiation proctitis according to some clinical trials 25 . In addition, endoscopic therapies have also been developed for the treatment of radiation proctitis, including laser therapies 26 , 27 , argon plasma coagulation 28 , 29 , radiofrequency ablation 30 , 31 and cryoablation 32 , 33 . However, these therapies of radiation proctitis still remain unsatisfactory and novel treatments are urgently needed.…”
Section: Discussionmentioning
confidence: 99%